Human gastric magnet-controlled capsule endoscopy conducted in a standing position: the phase 1 study - Cheng, Chun-sheng; Sun, Ting-ji; Zhang, Hou-de (BMC gastroenterology, 2019)
Current magnet-controlled capsule endoscopy (MCE) for the stomach is not yet satisfactory with respect to navigation control, especially in the gastric fundus and cardia. A newly developed MCE system conducted in a standing rather than supine position may improve capsule maneuverability within the stomach. The aim of this phase 1 study was to assess the feasibility and safety of this system for examining the human stomach in healthy volunteers. A cohort of 31 healthy volunteers were enrolled. Each swallowed a capsule after drinking water and gas producing agents intended to produce distention. Under the newly developed standing MCE system, subjects were examined endoscopically while standing with external guide magnets placed on the abdominal wall and left lower chest. Safety, gastric preparation, maneuverability, visualization of anatomical landmarks and the gastric mucosa, and examination time were the primary parameters assessed. The gastric preparation and examination procedures were well accepted by the subjects and there were no adverse events. Gastric examination took 27.8 ± 8.3 min (12-45 min). Gastric cleanliness was good in 24 participants (77.4%) and moderate in 7 participants (22.6%). Gastric distention was good in all of 31 participants (100%). Capsule maneuverability was also graded as good in all 31 subjects (100%), and manipulation in the fundus and cardia regions was as easy as that in the antrum and body. Visualization of the gastric cardia, fundus, body, angulus, antrum and pylorus was assessed subjectively as complete in all 31 subjects (100%). Visualization of the gastric mucosa was also good (> 75%) in all 31 subjects (100%). In areas where the mucosa could not be visualized, the low visibility was due to opaque fluid or foam. Polyps and erosive lesions were found in 25 subjects. MCE of the stomach conducted in a standing position is feasible and safe with satisfactory maneuverability.